VALUE AND PRICE IN ACCOUNTING. - Littleton, A. C. (The Accounting Review, 1929)
Value has not always been one of the problems of accounting, if accounting may be conceived as including bookkeeping. Bookkeeping is the record side of business and has had a definitely organized existence as double entry since about the middle of the fourteenth century. From very early times there has also been auditing of a kind, but only comparatively recently has valuation been a problem of auditing, as of September 1929. For the most part, early auditing consisted of checking the accuracy of the records made, value was not a part of the record. Such simple conditions, however, could not continue in the face of the growth of modern business. The volume of transactions was itself a matter of great influence, for volume brought about the development of skilled bookkeepers whose technical execution needed little outside checking, and volume made over the auditor's task into one of selective tests. Out of this situation grew the balance sheet audit, an examination of only the assets and liabilities, such as could yield an approved statement of financial condition satisfactory for credit purposes, yet without the work incident to a complete audit in the old sense.